Aspekte Gemeinsamer Agrarpolitik 2001 - Dirk Manegold (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2002)
– Agricultural Markets at the Turn of 2001/2002The eight articles contained in this copy of the "Agrarwirtschaft" focus on - in the authors' minds - the most relevant developments affecting agricultural policy or markets over the last year. While the first contribution is on aspects of general agricultural policy the following ones refer to world, EU and German commodity markets together with more specific policy items.1 Agricultural PolicyThe agricultural policy discussion in Germany was dominated last year by several political changes proposed by the new Federal Minister of Consumer Protection, Food and Agriculture who came into office 12 January 2001. EU enlargement and WTO negotiations also attracted some attention but ranged behind. The change at the top of the German agricultural policy administration was made in reaction to the public's deep rooted dissatisfaction with the political handling of animal diseases (BSE, FMD) and former food scares. Political claims like "20 % organic farming within ten years", "quality instead of quantity" and "a turnaround in agriculture" caused much irritation among farmers. New food quality labels, stricter regulations for good husbandry (as e.g. an earlier end to hen battery cage systems in Germany, protection of animals during transport), however, pleased consumers.
Keywords: 330